Another case of cryptic diversity in poison frogs (Dendrobatidae: Ameerega)description of a new species from Bolivia - Lötters, Stefan; Schmitz, Andreas; Reichle, Steffen; Rödder, Dennis; Quennet, Verena (Zootaxa, 2009)
We describe a new species of poison frog from the Serranías de Santiago and Chochis, isolated Precambrian sandstone massifs in the Chiquitanía region of Bolivia. The new species is morphologically similar to the Brazilian Ameerega braccata and A. flavopicta and best distinguished by larger adult size (27.57 mm versus < 22 mm in A. braccata) and coloration of ventral surfaces in life (light grey to light brown with black marbling versus yellowish white with occasional black marbling in A. flavopicta), respectively. The new species is genetically most closely related to A. flavopicta (uncorrected p-distances of the 16S mitochondrial rRNA gene ca. 2 %) but clearly differs in characteristics of its advertisement call (longer note duration, lower note repetition rate, lower number of pulses per note, and lower fundamental and dominant frequency). The new species can be commonly found in the vicinity of rocks, often near running water, and should be considered 'Least Concern' (LC) under IUCN Red List criteria.